Hover flies in Vietnam (Diptera: Syrphidae) - Thinh, Ta Huy (Academia Journal of Biology, 2012)
Hover flies (Syrphidae, Diptera) in Vietnam are represented by 57 species belonging to three subfamilies: Syrphinae, Eristalinae and Microdontinae. Subfamily Syrphinae includes three tribes: tribe Paragini with 1 genus; tribe Bacchini with 1 genus and tribe Syrphini with 13 genera. Subfamily Eristalinae includes seven tribes: tribe Cheilossini with 2 genera; tribe Merodontini with 1 genus; tribe Brachyopini with 1 genus; tribe Sericomyini with 1 genus; tribe Volucelini with 1 genus; tribe Eristalini with 4 genera; and tribe Milessini with 6 genera. Subfamily Microdontinae contains 1 genus. A species list of Hover flies in Vietnam is showed in accordance with Thompson et Vockeroth classification (2004) and keys to the tribes, genera and species are presented. The specimens of six species namely Scaeva opimius (Walker, 1852); Eosphaerophoria symmetrica Mengual, 2010; Eosphaerophoria vietnamensis Mengual, 2010; Neoascia anassa Reemer et Hippa, 2005; Pseudovolucella sinepollex Reemer et Hippa, 2008 and Pseudovolucella mimica Shiraki, 1930 were absent from my collection so that their taxonomic characteristics were gotten on the original description. Almost all of Syrphine species recorded in Vietnam are widely spread in Oriental region even many of them are worldwide distributed. Several of Syrphine flies such as Paragus serratus (Fabricius, 1805), Melanostoma univittatum (Wiedemann, 1824), Ischiodon scutellaris (Fabricius, 1805), Sphaerophoria indiana Bigot, 1884, Dideopsis aegrota (Fabricius, 1805), Episyrphus balteatus (De Geer, 1776) and Eupeodes confrater (Wiedemann, 1830) are of frequently occurence in Vietnam and all of them are predaceous in their larval development on Aphids. Within the Eristaline species flies, those of the tribe Eristalini show more common in Vietnam, with a high occurence of many species in the genera such as Phytomyia, Mesembrius, Eristalis and Eristalinus particularly the following species Eristalinus arvorum (Fabricius, 1787); Eristalinus quinquestriatus (Fabricius, 1794); Eristalinus quinquelineatus (Fabricius, 1781); Eristalis tenax (Linnaeus, 1758); Eristalis cerealis Fabricius, 1805; Mesembrius bengalensis (Wiedemann, 1819); Phytomyia zonata (Fabricius, 1787); Phytomyia errans (Fabricius, 1787) and Phytomyia chrysopygus (Wiedemann, 1830) are frequently occured.